Web-Based Scholarship Information System AT Darul Muttaqien Islamic Boarding School - Jejen Jaenudin; Fitria Rachmawati; Dahlia Widhyaestoeti; Zulkarnaen Noor Syarif; Fatimah Azzahra (Universitas Ibn Khaldun Bogor, 2024)
Darul Muttaqien Islamic Boarding School is an educational institution that provides various scholarships to its students. However, the selection system for receiving scholarships is still done manually using Microsoft Excel, so that the decision-making process becomes inefficient and less targeted. This research aims to design a web-based scholarship acceptance information system to improve the accuracy and efficiency of scholarship recipient selection. The method used in this research is the Weighted Product (WP) method that allows the selection of the best alternative based on five criteria: average report card score, parents' income, number of dependents, non-academic achievement, and social value aspects. The system was developed using PHP and MySQL as the main database. The implementation results show that the system runs well and is able to store and manage scholarship data in a more structured manner, where the process of inputting, editing, and deleting data can only be accessed by authorized users. With this system, the selection process of scholarship recipients becomes faster, more accurate, and more transparent, thus increasing the effectiveness of scholarship management at Darul Muttaqien Islamic Boarding School.